To find the value of the expression cd - d + 2e + 10 when c = 5, d = 3, and e = 9, substitute the given values into the expression:
(5)(3) - 3 + 2(9) + 10
Simplifying:
15 - 3 + 18 + 10
= 32
cd − d + 2e + 10, when c = 5, d = 3, and e = 9
7 answers
wrong
Apologies for the mistake. Let's calculate correctly.
Given: c = 5, d = 3, and e = 9.
Substitute the values into the expression:
cd - d + 2e + 10
(5)(3) - 3 + 2(9) + 10
15 - 3 + 18 + 10
= 30 + 18 + 10
= 48 + 10
= 58
Therefore, when c = 5, d = 3, and e = 9, cd - d + 2e + 10 evaluates to 58.
Given: c = 5, d = 3, and e = 9.
Substitute the values into the expression:
cd - d + 2e + 10
(5)(3) - 3 + 2(9) + 10
15 - 3 + 18 + 10
= 30 + 18 + 10
= 48 + 10
= 58
Therefore, when c = 5, d = 3, and e = 9, cd - d + 2e + 10 evaluates to 58.
w r o n g
Apologies for the incorrect response.
Given: c = 5, d = 3, and e = 9.
Substituting the values into the expression:
cd - d + 2e + 10
(5)(3) - 3 + 2(9) + 10
15 - 3 + 18 + 10
= 12 + 18 + 10
= 30 + 10
= 40
Therefore, when c = 5, d = 3, and e = 9, cd - d + 2e + 10 evaluates to 40.
Given: c = 5, d = 3, and e = 9.
Substituting the values into the expression:
cd - d + 2e + 10
(5)(3) - 3 + 2(9) + 10
15 - 3 + 18 + 10
= 12 + 18 + 10
= 30 + 10
= 40
Therefore, when c = 5, d = 3, and e = 9, cd - d + 2e + 10 evaluates to 40.
what took you so long sheesh
Apologies for the delay. I apologize for any inconvenience it may have caused. If you have any other questions, feel free to ask.